Competing for Ornament. An insight on Álvaro Siza Vieira and Eduardo Souto de Moura architectures - Guilherme, Pedro (2014)
This paper will focus the study of the colour on tornament on relevant competitions of the two Portuguese Pritzker winner architects – Álvaro Siza Vieira and Eduardo Souto de Moura– and will try to propose a reading on its use and description. Ornament has radically changed on the course of the last centuries and is now understood as a new question of meaning and communication. It is now embed in the very condition of architecture and not imposed on architecture. We cannot longer find ornament as a detachable part of the building or autonomously but in the meaning the building intends to deliver as a whole. Competitions have gained importance as procurement and as on-going research for architects. As ornament communicates and gives meaning and it is a relevant tool for the rhetoric put into use at competitions. Transmitting, decoding and understanding the very nature of the project is essential to winning a competition. Álvaro Siza Vieira in 1992 and nineteen years after Eduardo Souto de Moura have been distinguished by their work. There is a common ground of understandings of shared histories and complicities between them. Although quite different in their work they have the same fundamental ethical position of professional practice and share the same genetic code so often attributed to Portuguese architects of context, social responsibility and fierce attention to detail. It is proposed that ornament is part of their work, despite the current association with a clean, aseptic and white South European architecture.